Asymmetric piperidine synthesis - Lewis, Neil (1995)
It has been demonstrated that bakers' yeast reduction of 1-tert-butyl-2-methyl 3-oxo-piperidine-1,2-dicarboxylate gives (2R, 3S), 1-tert-butyl-2-methyl 3-hydroxy-piperidine-1,2-dicarboxylate in 80% chemical yield with >99% d.e. and >97% e.e. Also bakers' yeast reduction of 1-tert-butyl-3-ethyl 4-oxo-piperidine-1,3-dicarboxylate gives (3R, 4S), 1-tert-butyl-3-ethyl4-hydroxy-piperidine-1,3-dicarboxylate in 74% chemical yield with >99% d.e. and >93% e.e. The optical purity and absolute configurations of the hydroxy-ester derivatives were determined by conversion into the corresponding chiral bis-tosylate derivatives of 2- and 3-piperidinemethanol respectively.